Imposition of Land & Building Rights Acquisition Duty Taxes Dependent on Certificate of Property Rights in the Implementation of Complete Systematic Land Registration - ZA, Arief Febriyanto; Hafidz, Jawade (Jurnal Konstatering, 2022)
This study aims to find out & analyzeprocedures for the imposition of tax on the acquisition of land & building rights payable on certificates of ownership in the implementation of a complete systematic land registration, as well as to know & analyzelegal consequences of the imposition of tax on the acquisition of land & building rights owed on certificates of ownership in the implementation of a complete systematic land registration.The approach method in this research is normative law (doctrinal). Normative legal research that is more specific discusses legislation or is also called normative juridical. Based on the results of the study, it was concluded: 1) Issues with Payable PPh & BPHTB in the implementation of Complete Systematic Land Registration (PTSL) which are regulated in Article 33 of Ministerial Regulation ATR/Ka BPN Number 6 of 2018 which provides space for convenience in implementing the PTSL Program, for those who do not or have not able to pay PPh & BPHTB by making a statement of PPh & BPHTB Outstanding, the certificate of land rights can still be issued. However, provisions regarding PPh & BPHTB payable in Complete Systematic Land Registration activities still require separate arrangements, especially regarding the billing mechanism & payment time that must be made by PTSL participants; 2)The provisions of Article 33 of Permen ATR/Head of BPN Number 6 of 2018, vertically, contradict the provisions of Articles 3 & 7 PP Number 34 of 2018 & Articles 90 & 91 of Act No. 28 of 2009. Legal consequences of the provisions of Article 33 of Permen ATR/Head of BPN Number 6 of 2018, namely causing legal uncertainty, legal injustice, & not fulfilling the legal force of land rights certificates as a strong means of proof. Legal uncertainty occurs because there is dualism in regulations governing procedures for paying PPh & BPHTB as well as uncertainty regarding the payment mechanism. Legal injustice occurs due to differences in the provisions for issuing certificates between Article 33 of Permen ATR/Head of BPN Number 6 of 2018 & Articles 3 & 7 of Government Regulation Number 34 of 2018 & Articles 90 & 91 of Act No. 28 of 2009, because of this.Keywords: Debt; Outstanding; Tax.